Academic training in the Bachelor’s Degree in Management for Urban and Regional Development, FTU-UNSL. Between Complexity and Transdiscipline - Cresmani, Mónica Liliana; Ciccarone, María Inés; Silvestre, Luciana Sol; Resio, Ana Sofía (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The reality of academic training in Management is a great challenge for most professors who are used to working with certainties and truths, with predictability and stability. Thinking and performing "management" is a challenge of every moment because the realities in which we move have changed and change permanently and, at the same time, institutions or people are participants in these transformations of social scenarios. To manage is an integral action, it is a work and organization process in which different views, perspectives and efforts are coordinated to advance effectively towards institutionally assumed objectives that must be adopted in a participative and democratic way. Academic training must consider this transformation in the construction of knowledge and generate a non-linear learning process typical of the dynamic events of life. Today we face uncertain and fluid times with intellectual tools from other times, from other times, when reality was observed as stable, homogeneous and determined. That is why we have to learn to differentiate and distinguish, without having to separate. In this sense, there are two pairs of concepts that are clearly distinguishable and not separable: on the one hand, the concepts of complexity and complex thinking and, on the other hand, transdisciplinary knowledge. While historically the division of the sciences and the emergence of the subject-object duality introduce a fragmentation that leads to specialization, today we propose an academic training in Management that not only seeks the crossing and interpenetration of the different disciplines, but also aims to erase the boundaries that exist between them to integrate them into a single system based on the understanding of the complexity of the present world, starting from the simplest to the most complex objects and across disciplines and beyond all disciplines.